Spatio-temporal variation and future risk assessment of projected drought events in the Godavari River basin using regional climate models - Soumyashree Dixit (IWA Publishing, 2021)
The study focused on the Godavari River basin to understand the alteration in the drought phenomenon for future scenarios. The Standardized Precipitation Evapotranspiration Index (SPEI)-3 is calculated from Climate Research Unit 4.03 precipitation, and minimum and maximum temperatures. The drought magnitude and characteristics are determined using SPEI, which considers both precipitation and temperature data as input variables. The Mann–Kendall trend analysis is performed to identify the trend associated with drought characteristics. The basin is divided into six homogeneous regions using K-means clustering algorithm. The reliability ensemble averaging method is used for ensemble averaging of regional climate models (RCMs). The drought frequency analysis is carried out using trivariate copula for reference and future time periods. Variations in the drought characteristics are observed in the future scenarios with respect to the reference period. The drought duration, severity and peak for different climate divisions showed an increasing trend in future time period, especially in the case of RCP8.5 scenarios. The return periods of future droughts based on weighted-average RCMs under the two scenarios showed the possibility of more frequent droughts in the future (2053–2099) than in the past (1971–2017). HIGHLIGHTS The Standardized Precipitation Evapotranspiration Index (SPEI) for historical and future periods is computed.; The SPEI is used to assess drought characteristics in the Godavari River basin.; The river basin is divided into six regions using K-means clustering algorithm.; The trend analysis is carried out using historical and future drought characteristics.; Future drought return periods are computed using trivariate copula.;